Interfaith Dialogue and Unity in Diversity: A Critical Discourse Analysis of Pope Francis’s Speeches (2024) in Jakarta - Tano, Andreas (Jurnal Pendidikan Makarios, 2025)
This study employed Critical Discourse Analysis (CDA), a qualitative method to examine Pope Francis’s (2024) speeches in Jakarta, integrating ​Teun van Dijk’s socio-cognitive framework​ (2006) and ​Ruth Wodak’s discourse, historical approach (2001). As the result, the findings emerge: 1) The Pope’s rhetorical strategies; such as, ​inclusive pronouns​ (e.g., “we”) and ​metaphors​ like “bridges of dialogue”, construct collective identity and align with Indonesia’s national motto "Bhinneka Tunggal Ika" (Unity in Diversity), framing interfaith harmony as a moral imperative. 2) The speeches depict power dynamics by positioning the Church as a “servant of the common good,””compassion,” “mercy,” and “inclusivity” which aligns with the Islamic principles (e.g., rahmatan lil ‘alamin), legitimizing the alignment to state policies while subtly outlining systemic inequities, in line with van Dijk’s concept of symbolic power. 3) The discourse reconciles historical tensions by referencing Indonesia’s conflict struggles and avoiding contentious terms like “conversion,” reflecting Wodak’s emphasis on the role of historical context in shaping communication. The Pope’s rhetoric strategically engages Indonesia’s past events and present-day religious policies to foster reconciliation and legitimize the Church’s role in a pluralist society. Through textual analysis, contextual triangulation with policy documents, and ethical rigor, the study draws attention to the Pope’s strategic balance of affirming state-endorsed pluralism while advocating for grassroots justice, demonstrating CDA’s efficacy in decoding religious diplomacy in diverse societies.